The effect of a source-contacted light shield on the electrical characteristics of an LTPS TFT. (3rd July 2017) - Kim, Miryeon; Sun, Wookyung; Kang, Jongseuk; Shin, Hyungsoon
Abstract: The electrical characteristics of a low-temperature polycrystalline silicon thin-film transistor (TFT) with a source-contacted light shield (SCLS) are observed and analyzed. Compared with that of a conventional TFT without a light shield (LS), the on-current of the TFT with an SCLS is lower because the SCLS blocks the fringing electric field from the drain to the active layer. Furthermore, the gate-to-source capacitance ( C gs ) of the TFT with an SCLS in the off and saturation regions is higher than that of a conventional TFT, which is due to the gate-to-LS capacitance ( C g-LS ). The electrical characteristics of the TFT with an SCLS are thoroughly investigated by two-dimensional device simulations, and a semi-empirical C g-LS model for SPICE simulation is proposed and verified.